Lygosoma Punctata (Spotted Supple Skink). Endoparasites - Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2009)
Lygosoma punctata is a diurnal, fossorial skink that is widepread in Sri Lanka, India, Bangladesh, and Pakistan (Das and de Silva 2005. A Photographic Guide to Snakes and Other Reptiles of Sri Lanka. Ralph Curtis Publ., Sanibel Island, Forida. 144 pp.). To our knowledge, the only helminth recorded from L. punctata is the nematode, Thelandros sp. (Lakshimi et al. 1985. Ind. J. Helminthol. 2:115–125). The purpose of this note is to add the nematode Parapharyngodon adamsoni to the helminth list of L. punctata.